Small-scale gold mining in southern Africa - Joubert, Barend Daniel (Rhodes University, Faculty of Science, Department of Geology, 1992)
The general characteristics of gold deposits are reviewed, and a classification of gold deposits based on mineability is proposed. Evaluation, mlnlng and beneficiation methods are briefly discussed. It is concluded that the most viable targets for small-scale companies comprise deposits that require the least pre-production time and expense. Great potential exists for the small-scale reclamation of gold from tailings dumps and abandoned mines in Southern Africa. There is also potential for developing new smallscale gold mines in the Archaean greenstone terranes of the Zimbabwean and Kaapvaal cratons.
Keywords: Gold mines and mining -- South Africa; Abandoned mines; Abandoned mines -- South Africa